Age-Related Changes in Spatial Navigation Are Evident by Midlife and Differ by Sex. (May 2021) - Yu, Shuying; Boone, Alexander P.; He, Chuanxiuyue; Davis, Rie C.; Hegarty, Mary; Chrastil, Elizabeth R.; Jacobs, Emily G.
Accumulating evidence suggests that distinct aspects of successful navigation—path integration, spatial-knowledge acquisition, and navigation strategies—change with advanced age. Yet few studies have established whether navigation deficits emerge early in the aging process (prior to age 65) or whether early age-related deficits vary by sex. Here, we probed healthy young adults (ages 18–28) and midlife adults (ages 43–61) on three essential aspects of navigation. We found, first, that path-integration ability shows negligible effects of sex or age. Second, robust sex differences in spatial-knowledge acquisition are observed not only in young adulthood but also, although with diminished effect, at midlife. Third, by midlife, men and women show decreased ability to acquire spatial knowledge and increased reliance on taking habitual paths. Together, our findings indicate that age-related changes in navigation ability and strategy are evident as early as midlife and that path-integration ability is spared, to some extent, in the transition from youth to middle age.